Numerical modeling of the Hágöngur geothermal reservoir in Central Iceland - Muguruza, Ximena Guardia, 1989- (2015)
The Hágöngur geothermal area in Central Iceland is among the larger geothermal areas of the country. Surface exploration studies including geology and geothermal manifestations mapping, Transient Electromagnetic (TEM) resistivity surveys, Magnetotelluric (MT) soundings and geothermometry assessments have been conducted in the area, along with the drilling of one deep exploration well (HG-01) near the center of the resistivity anomaly. The present study integrates all physical, geological and geochemical data available by developing conceptual and numerical models of the system, in order to provide insight into the reservoir’s behavior for future utilization of the geothermal fluid. Resistivity, lithology and stratigraphy models of the reservoir were created using the RockWorks16 software based on MT resistivity measurements, lithology data of the HG-01 borehole and geological and topographical information of the area. Two different versions of the conceptual model were built based on these data, plotting stratigraphy units, cap rock, faults, heat source, temperature gradients and flow pattern. Further numerical models were developed matching up stratigraphic elevation information, rock properties and downhole temperature and pressure values using the TOUGH2 simulator via the graphical user interface PetraSim. PetraSim was also employed to define and calibrate cell-specific data such as heat sources and initial conditions to create two versions of the natural state model of the reservoir. Landsvirkjun